TINJAUAN YURIDIS UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN LINGKUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP MENGENAI AMDAL DALAM IZIN PERTAMBANGAN - La Ode Abdul Hamid; Hendrik Ruben Gelong; I Komang Sutrisnayasa (Jurnal Ilmu Hukum Kanturuna Wolio, 2023)
This research is a normative juridical law writing using statutory and conceptual approaches. The results of the study show that in the process of preparing the EIA, it is mandatory to be accompanied by community participation, and environmentalists from the beginning to the end of the business/activity which will form decisions in the EIA process in accordance with the principles of sustainability and sustainability contained in article 2 of the UPPLH. EIA is needed to minimize negative impacts on the environment, avoid conflicts between the government and the community and realize environmentally sustainable development. In addition, the urgency of enforcing an Environmental Impact Analysis for mining is that the policies or decisions that will be taken will be more appropriate, and the community will know what impacts will occur (positive and negative) and what efforts will be made to reduce the negative impacts.